The Role of Communication Skills in Guided Inquiry Process to Improve Critical Thinking Skills - Elma Pujiana; Eli Rohaeti; Suyanta Suyanta; Lisya Asmiati; Dwiani Ratna Sari; Syaza Syahana (Jurnal Penelitian Pendidikan IPA, 2024)
This article examines how in an educational setting communication skills can enhance critical thinking abilities through guided inquiry. Human resources (HR) must be improved in light of the Industrial Revolution 4.0, but obstacles to learning include low student engagement, a lack of enthusiasm, and a lack of critical thinking abilities. Although communication skills are frequently a barrier, guided inquiry is recognized as a learning model capable of advancing students' critical thinking abilities. The activity steps in guided inquiry are covered in this article, along with pertinent communication skills such as explanation of delivery, material mastery, group interaction, and responding. It is highlighted how critical thinking abilities and communication skills are linked in 21st-century learning. It is widely acknowledged that effective verbal, written, and listening communication skills are essential for guided inquiry. Source triangulation was employed as a qualitative research method with a post-positivism approach to gather data. The article emphasizes how communication skills help students develop their critical thinking abilities by enabling them to assess and connect information to a wider context in addition to gathering and analyzing it. The conclusion highlights the need of communication abilities